Pengaruh Pendidikan Kesehatan Terhadap Kebiasaan Olahraga dan Nyeri Haid pada Remaja Putri Kelas XII di SMA N 1 Mlati - Isnayanti, Azamita; Istiyati, Siti (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2024)
Dysmenorrhea is pain in the lower abdomen during menstruation. Therefore, many efforts have been made to reduce menstrual pain complaints, namely by pharmacological and non-pharmacological methods. For Non- pharmacological intervention, one of which is regular exercise such as jogging, running, cycling, swimming and gymnastics 3-5 times a week. One way to improve the sports habits of these teenagers is through health education. The research objective was to determine the effect of health education on exercise habits and menstrual pain in class XII female adolescents at SMAN 1 Mlati. The research design used was a pre-experimental design with the one group pretest-posttest method. The population of this study were all female students of class XII at SMAN 1 Mlati who experienced menstrual pain as many as 50 respondents with a sampling technique using total sampling. Pain scale was determined through a verbal descriptor scale sheet. The analysis technique used univariate and bivariate analysis. Bivariate analysis used the Wilcoxon signed ranks test. The results of the Wilcoxon signed rank test on both variables show that Asymp. Sig. (2-tailed) is 0.000, because the sig. (2- tailed) 0.000 <0.05. It can be concluded that there is an influence of health education on exercise habits and menstrual pain in class XII female adolescents at SMAN 1 Mlati. As a suggestion, sport can be used as an alternative intervention that can be done to relieve menstrual pain.